Coping with diabetes during the COVID – 19 lockdown in India: Results of an online pilot survey - Nachimuthu, Sukanya (Diabetes Metab Syndr, 2020)
AIM: The management of diabetes has become a challenge due to the COVID 19 lockdown. An online-based pilot survey was conducted to study how people with diabetes were coping with their Diabetes during the COVID - 19 lockdown. METHOD: The questions were designed in an online survey, Survey Monkey, to conduct this cross-sectional study. The link was generated and sent to 100 registered patients of the MV Hospital for Diabetes Royapuram who had not contacted the hospital after the lockdown announcement. The survey was done between April 1 and April 15, 2020.Oral consent was obtained through telephone before the link was sent by Whatsapp to them.The questionnaire consisted of questions on home blood glucose monitoring, regularity in doing their physical activity and dietary compliance and anxiety about the viral infection. RESULTS: 92% of the participants had Type 2 diabetes. Only 28% of the participants were checking their blood glucose levels regularly. 80% of the participants mentioned that they were following regular exercise and diet control during the lockdown period. 40% of the participants were anxious about the Covid infection. CONCLUSION: SMBG needs to be practiced on regular basis, especially among the patients with diabetes on insulin therapy. Most of the people surveyed were coping well with their Diabetes. Patients have reported that they were able to maintain proper dietary compliance and be more physically active at home during this lockdown. These findings need to be ascertained in larger sample of patients.